Comparative Efficacy and Safety of Finerenone, Eplerenone, and Spironolactone on Cardiorenal Outcomes in Type 2 Diabetes with Chronic Kidney Disease: A Systematic Review and Network Meta-Analysis - Krismeikesari Krismeikesari (HM Publisher, 2026)
Mineralocorticoid receptor antagonists (MRAs) are critical for managing chronic kidney disease (CKD) in type 2 diabetes (T2D), yet a